Pengaruh Reputasi KAP, Profitabilitas, dan Debt To Equity Ratio Terhadap Audit Delay: (Studi Pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019 - Melia Wida Rahmayani; Ayu Gumilang Lestari; Yogi Ginanajar; Wulan Riyadi (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2022)
Food and beverage companies listed on the Indonesia Stock Exchange found 3 companies listed as experiencing delays of 92 to 157 days with the influencing factors, namely KAP's reputation, profitability, and debt to equity ratio. This study aims to determine the effect of KAP reputation on audit delay, to determine profitability to audit delay, to determine debt to equity ratio to audit delay, in food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2019 period.This study uses quantitative methods and uses secondary data. Secondary data was obtained from the Indonesian Stock Exchange Investment Gallery, Majalengka University and through thewebsite official IDX. The population in this study were 24 companies using purposive sampling method with a total sample of 36 consisting of 12 companies with a long research period of 3 years. The data analysis technique used is descriptive analysis, classical assumption test, multiple regression analysis and hypothesis testing with the help of SPSS version 21 program.The results of this study indicate that KAP reputation has no significant effect on Audit Delay. Profitability has no significant effect on Audit Delay. Debt to Equity Ratio has no significant effect on Audit Delay.